Scenario Thinking Preparing Your Organization for the Future in an Unpredictable World - Cairns, George (Springer International Publishing, 2018)
Develops scenario planning methods in ways that link scenario analysis to improved decision making, engage time-poor senior decision makers, attenuate decision makers' tendency to deflect responsibility for bleak, negative scenario outcomes, and enhance causal analysis within scenario-storyline development. What if? Two of the most powerful - and frightening - words in business. Almost as bad as "I didn't see that coming." Some things that transform the marketplace overnight come from nowhere. Some things that create potentially critical under-performance are genuinely unforeseeable. Sometimes it is impossible to predict how a change in an organizational strategy will play out. Some things and sometimes - but not many and not often. Decision makers in organizations face more-and-more complex and ambiguous problems that need to be addressed under time pressure - and the need for practical decision support has become essential. The range of methods in this book will enable you to be prepared, proactive and resilient no matter what the future brings. Based on up-to-date academic research and years of application and iteration in the real world, this book, illustrated with examples of the value delivered in Europe, Australia and the Middle East, will transfer practical skills in scenario thinking using step-by-step instructions. This thoroughly revised and expanded second edition introduces these new approaches in detail, with clear guidelines and examples to enable the reader to select and implement the most appropriate scenario method to suit the issue at hand - considering the timeframe for its investigation, the resources available and the outcomes expected.